Can unilateral, progressive or sudden hearing loss be immune-mediated in origin?. (3rd August 2017) - Atturo, Francesca; Colangeli, Roberta; Bandiera, Giorgio; Barbara, Maurizio; Monini, Simonetta
Abstract: Objective: The aim of the present study was to demonstrate that the positivity of nonspecific immunological tests could be found not only in bilateral hearing loss but also in unilateral cases, either sudden or progressive. Method: An observational case series study included subjects suffering from unilateral or bilateral, sudden or progressive, symmetric or asymmetric sensorineural hearing loss (SNHL). All the patients underwent pure tone audiometry and the following battery of blood exams: anti-nuclear antibody (ANA), extractable nuclear antigen (ENA) antibody screening, anti-thyroperoxidase (anti-TPO), anti-thyroglobulin and anti-smooth muscle antibody (ASMA). Results: The positivity to nonspecific immunological test was found in nearly 70% of the study groups. ASMA and ANA were found to be present in both bilateral and unilateral cases, without statistical difference. Considering the correlation between positivity/negativity and systemic autoimmune pathologies, in the bilateral forms of hearing loss, a high incidence of thyroid pathologies has been identified, with a higher percentage of systemic autoimmune diseases in respect to the normal population. Conclusions: The nonspecific autoimmune tests are worth to be performed also when SNHL is not bilateral and progressive, since an immunological mechanism could also underlie unilateral and sudden SNHL cases.